Above‐ and below‐ground biodiversity responses to the prolonged flood pulse in central‐western Amazonia, Brazil. Issue 3 (3rd December 2021) - Bredin, Yennie K.; Hess, Laura L.; Scabin, Andressa B.; Dunthorn, Micah; Haugaasen, Torbjørn; Peres, Carlos A.; Nilsson, Henrik R.; Antonelli, Alexandre; Ritter, Camila D.
Abstract: Amazonia encompasses extensive forests in areas that are periodically inundated by overflowing rivers. The inundation depth and duration vary according to the slope of the terrain and distance to major water bodies. This creates a flooding gradient from the lowest lying seasonally flooded forest up into the unflooded forest, which directly affects the biota. However, the effect of this gradient on soil organisms remains elusive. Here, we use DNA metabarcoding to estimate prokaryote and eukaryote diversity from soil and litter samples along the flooding gradient in central‐western Amazonia using 16S and 18S gene sequences, respectively. We characterize the below‐ground diversity and community composition based on amplicon sequence variants (ASVs). We examine relationships between the soil biota and the flooding gradient, soil properties, and above‐ground woody plant diversity. The flooding gradient does not explain below‐ground biodiversity, nor is below‐ground diversity explained by the above‐ground woody plant diversity. We uncover several taxonomic groups—such as Patescibacteria—not previously reported from Amazonian seasonally flooded forests. The flooding gradient and woody plant diversity partly explain the community composition of soil bacteria. Although the effects of the flooding gradient, soil properties, and above‐ground woody plant diversity are difficult to quantify, our results indicate that flood stress may influence below‐ground bacterial community composition. Abstract : Amazonia encompasses forests that grow in areas that are periodically inundated by overflowing rivers. Here, we use DNA metabarcoding to estimate prokaryote and eukaryote diversity from soil and litter samples across four flood levels in a seasonally flooded forestscape in central‐western Amazonia. The below‐ground diversity was not explained by the above‐ground woody plant diversity. The flooding gradient and woody plant diversity did, in part, explain the community composition of soil bacteria.